Forensic pathology reviews volume 6 - Turk, Elisabeth E. (Forensic pathology reviews, 2011)
Fresh research has opened up new vistas in forensic pathology that are allowing for closer national and international cooperation between pathologists and scientists in a range of medical and scientific disciplines. At the same time, autopsy and laboratory techniques are undergoing rapid evolution, with new procedures coming on stream while existing processes yield additional—and more accurate—results.   This sixth volume of reviews in forensic pathology provides professionals working in the field with cutting-edge material on the latest key advances in the fields of traumatic death, sudden natural death and death time estimation. Now with numerous color illustrations, the book gives forensic experts across the world a fully up-to-date guide to contemporary procedures and theory in forensic science and medicine. The chapters cover an exhaustive range of aspects in the discipline, from the analysis of sudden natural deaths in infancy and childhood to the cardiac proteomics approach in the study of cases involving sudden cardiac death. Other specialist chapters deal with the forensic investigation of deaths in aviation and as a result of accidents involving all-terrain vehicles. The volume covers fresh research in the use of protein markers for the estimation of post-mortem intervals, and features a chapter telling the story of the medico-legal investigation into the deaths resulting from the 9-11 terrorist attacks on the World Trade Center.Comprehensive and current, this fresh volume of reviews is an essential resource for professionals who need to stay ahead of the game in a fast-moving and exciting field of scientific endeavor. Sudden natural deaths in infancy and childhood -- Post-mortem investigation of sudden unexpected death in infancy (SUDI): role of autopsy in classification of death -- Sudden death from pulmonary causes -- Sectioning of the heart, searching for pathology under the microscope and the cardiac proteomics approach in the study of sudden cardiac death cases -- Endocrine disorders with potentially fatal outcome -- Sudden death from infectious disease -- Aviation deaths -- Fatalities in general aviation: from balloons to helicopters -- The 9-11 attacks: the medicolegal investigation of the world trade center fatalities -- Injuries and fatalities in all-terrain vehicle crashes -- Advances in entomological methods for death time estimation -- Tissue fluorescence spectroscopy in death time estimation -- Heat-flow finite element models in death time estimation -- The use of protein markers for the estimation of the postmortem interval -- Alcohol and drug fatalities in transportation – forensic-toxicological implications.